Genetic, clinical, and biochemical profiling of Gilbert syndrome in a Nepali cohort: High prevalence of the UGT1A1 c.-3279T>G polymorphism and correlation with hematological parameters - Pragya Gautam Ghimire; Prasanna Ghimire; Rajan Pande (PLoS ONE, 2026)
Introduction Gilbert Syndrome (GS) is a common hereditary disorder characterized by intermittent jaundice. The pathogenesis is unconjugated hyperbilirubinemia due to reduced hepatic UDP-glucuronosyltransferase 1A1 (UGT1A1) activity. Its genetic basis relies on c.-3279T > G polymorphism (UGT1A1*60), which reduces gene transcription by approximately 40%, and is highly prevalent in Asian populations. Aims This study aimed to profile the genetic, biochemical, and clinical characteristics of individuals with clinical features of GS in Nepal and examine correlations between UGT1A1 genotypes and hematological parameters. Methods This study utilized a prospective descriptive design supplemented by a retrospective review of medical records, including 75 patients with isolated unconjugated hyperbilirubinemia. Prospective recruitment and data collection were conducted from July 18, 2025, to November 30, 2025. Medical records from outside facilities were accessed for research purposes from July 18, 2025, to November 30, 2025, covering records dating back to January 1, 2021. Patients underwent ARMS-PCR genetic testing for the UGT1A1 c.-3279T > G variant.Patients with hemolysis or hepatobiliary disease were excluded. Genetic confirmation of GS was based on the presence of the G allele. Results Mean age of cohort was 28.9 ± 10.4 years (range: 14–55), with a male predominance (69.3%). Genotype distribution revealed 66.7% homozygous mutant (G/G), 29.3% heterozygous (G/T), and 4% wild-type (T/T), yielding a G allele frequency of 81.3%. Mean bilirubin levels showed a genotype-phenotype correlation: G/G (4.3 ± 1.1 mg/dL), G/T (3.2 ± 0.9 mg/dL), and T/T (2.4 ± 0.3 mg/dL). Hematological parameters were within normal reference ranges across all genotypes, confirming the non-hemolytic nature of the condition. No hepatosplenomegaly was detected on ultrasonography. Conclusion This study demonstrates an exceptionally high prevalence of the UGT1A1*60 G allele among individuals with clinical features of GS in Nepal. These findings reaffirm the benign, non-hemolytic character of GS and underscore the diagnostic and pharmacogenetic utility of UGT1A1 genotyping in the Nepali population.